Identification of the woody biomasses in Southwest, Nigeria as potential energy feedstocks in thermal power plants for air pollution control. Issue 1 (1st January 2021) - Elehinafe, F. B.; Okedere, O. B.; Sonibare, J. A.; Mamudu, A. O.
Abstract: This study identified one hundred samples of woody biomasses in the southwest, Nigerian. The woody biomass samples identified were collected from different saw mills, farms and kitchens in Osun State, Nigeria. The identification of the woody biomass samples was done using literature materials and at a herbarium in the Botany Department, Obafemi Awolowo University, Nigeria, using the vegetative parts of their trees. The identification was carried out to know the numerical availability, the family or English names, the common names and the botanical names of the southwest Nigeria woody biomasses. From the findings, 100 samples of the woody biomasses were identified of 39 families and classes of hard woody biomasses and soft woody biomasses out of which only two are soft and rest are hard. It was discovered that Southwest, Nigeria has the capacity to embark on the massive production of these woody biomasses identified due to her land mass of 77, 818 km 2 comprising 85 forests. In conclusion, serious investment in the propagation of these energy crops would lead to the production of woody masses to serve as feedstocks in thermal power plants for sustainability in power supply, air pollution control and employment opportunities.